Supervisi Klinis Pengawas Dalam Meningkatkan Kinerja Guru di SMP Jati Agung Wage Kecamatan Taman Sidoarjo - Onik Zakiyyah; Abdullah Abdullah (LP2M Institut Agama Islam Nazhatut Thullab Sampang, 2022)
This study aims to determine and analyze the teacher's performance at Jati Agung Wage Junior High School, Taman Sidoarjo District, the process of clinical supervision of supervisors in improving teacher performance at Jati Agung Wage Junior High School Taman Sidoarjo. Wage Taman Sidoarjo.The research method in this study uses a descriptive research approach, because the discussion can be done by describing or describing facts in the form of a comprehensive narrative about situations and events in a systematic and factual manner regarding the factors, properties and relationships between phenomena that are owned to carry out research. base accumulation. In this study, the researcher uses qualitative methods, qualitative research is research that is intended to understand the phenomenon of what is experienced by the research subject, for example behavior, perception, motivation, action and others, holistically and by way of description in the form of words. and language, in a particular natural context and by utilizing various natural methods. Data collection techniques in this study used interview, observation and documentation techniques.The results showed that the role of school supervisors in improving the performance of PAI teachers through clinical supervision went well in accordance with their duties and functions, but their optimization needed to be improved. This can be seen from the success of teachers who are able to compile syllabus and design lesson plans in accordance with curriculum policies, teachers are able to make semester and annual programs and are able to organize teacher administration tools well, although supervisor visits to schools have not been maximized. In addition, teachers are able to determine strategies or learning methods that can develop various potentials of students. Although there are still some obstacles in the implementation of guidance carried out by school supervisors in improving the performance of PAI teachers, the role of supervisors with clinical supervision is very important because it can provide many benefits for teachers.